A Review of Self-Determination Theory’s Basic Psychological Needs at Work - Van den Broeck, Anja; Ferris, D. Lance; Chang, Chu-Hsiang; Rosen, Christopher C. (Journal of Management, 2016)
Self-determination theory (SDT) conceptualizes basic psychological needs for autonomy, competence, and relatedness as innate and essential for ongoing psychological growth, internalization, and well-being. We broadly review the literature on basic psychological need satisfaction at work with three more specific aims: to test SDT’s requirement that each basic psychological need should uniquely predict psychological growth, internalization, and well-being; to test whether use of an overall need satisfaction measure is appropriate; and to test whether the scale used to assess basic psychological needs influenced our results. To this end, we conducted a meta-analytic review of 99 studies with 119 distinct samples examining the antecedents and consequences of basic need satisfaction. We conclude with recommendations for addressing issues arising from our review and also identify points for future research, including the study of need frustration and culture, integrating the basic needs with other motivation theories, and a caution regarding the measures and methods used.